Mechanical and thermal analysis of self-curing concrete modified with polyethylene glycol-400 - Ruhal Pervez Memon; Alyas Khan Mandokhail; Jabir Hussain Memon; Muhammad Noor Kakar; Irfan Ali Chandio; Gohar Nadeem (Mehran University Research Journal of Engineering and Technology)
The development of concrete microstructures through curing enhances the material's performance and longevity. As water resources become increasingly scarce, there is an urgent need for research on water conservation in concrete. As a result, efforts have been made to develop self-curing concrete by employing polyethylene glycol 400 (PEG-400) as a self-curing ingredient. Work is frequently conducted in areas with severe water shortages when using purifying water is not financially feasible. The present investigation involves the use of a self-curing agent, PEG-400, at concentrations of 0%, 0.5%, 1%, and 2% by weight of cement. After 28 days of curing, the compressive strength, density, and appearance of conventional and self-cured concrete mixtures of M30 grades were examined. The thermal response of controlled and optimized self-curing concrete was investigated at elevated temperatures of 200°C, 400°C, 600°C, 800°C, and 1000°C, with a Continuous heating duration of 6 hours and after that furnace cooling was adapted, to analyze the density and residual compressive strength of controlled and optimized self-curing concrete. At 0% PEG-400, the baseline strength was 37.35 MPa. The optimal concentration of PEG-400 in M30 grade concrete was found to be 0.5% by weight of cement, which yielded a maximal strength of 47.87 MPa and a workability of 70 mm. The residual compressive strength of optimised self-curing concrete decreases by up to 15.56%, while that of controlled self-curing concrete decreases by up to 38.17% when the temperature is raised to 1000 °C in thermal behaviour analysis. The loss of compressive strength in controlled self-curing concrete is 22.61% higher than that in optimal self-curing concrete. It is determined that the self-curing approach would improve concrete qualities in terms of fire-resistant construction. Concrete sample containing 0.5% PEG-400 exhibited minimal evident evidence of spalling when heated up to 1000°C. Taking all considerations into account, the self-curing concrete containing 0.5% PEG-400 exhibited satisfactory performance, delivering all the required concrete properties.